THE INFLUENCE OF GROSS PROFIT MARGIN AND RETURN ON ASSET ON STOCK PRICES WITH PROFIT GROWTH AS AN INTERVENING VARIABLE - Vidiyawati, Wina; Siregar, Qahfi Romula (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine whether there is an effect of Gross Profit Margin and Return On Assets on Stock Prices with Profit Growth as an intervening variable in Mining Companies in the Coal Sub-sector Listed on the Indonesia Stock Exchange 2018-2022. The approach used is an associative approach, with the sampling criteria using the Purposive Sampling Technique, which is a sampling technique for data sources with certain considerations, so that out of 28 populations only 6 samples are obtained which can be examined. Data collection techniques using documentation studies. The data analysis method used in this study uses Partial Least Square (PLS). The results of the study prove that there is a significant effect between Return On Assets on Profit Growth, there is no significant effect between Gross Profit Margin on Stock Prices, there is no significant effect between Return On Assets on Stock Prices, there is no significant effect between Gross Profit Margin on Profit Growth, there is no significant effect between stock prices on profit growth, profit growth does not mediate the effect between gross profit margin on stock prices, profit growth does not mediate the effect between return on assets on stock prices .